Analysis of the Batik Tutur Motif on 'Justin Holiday' Clothing. - Fauzan, Muhammad (ARTCHIVE: Indonesian Journal of Visual Arts and Design, 2024)
Unearthing the original Blitar batik is not an easy task. The existence of this batik was first discovered through black-and-white photos found in old Dutch colonial archives, where it was written: "Batik Afkomstig Uit Blitar, 1902" in Dutch, which means 'Batik originating from Blitar, 1902.' Blitar Regency has batik motifs that carry deep meanings with diverse patterns. This research was conducted to identify the motifs, batik patterns, colors, and meanings found in Blitar Regency’s batik. To gather this information, a descriptive qualitative method was used, with observation and direct interviews as the techniques. The research results prove that Blitar Regency has "Batik Tutur", a type of batik that is a source of pride for the Blitar community. The word 'tutur' comes from the Javanese word 'pitutur' in ancient texts, which means advice. This is evident from the Batik Tutur motif, which has symbols in the shapes of animals and plants interconnected to form a pattern resembling a storyline filled with advice, symbolizing the noble values of local culture that should be emulated. Over time, Batik Tutur has undergone several innovations, enhancing its value and enabling it to reach international markets, even being favored by NBA player Justin Holiday. This has made Batik Tutur increasingly famous and appreciated by many for its uniqueness and distinctiveness